Family Policy and Stigmatisation of Single-mother Families - Skubiejute, Greta (Socialinė teorija, empirija, politika ir praktika, 2023)
This article investigates the stigmatisation of single-mother families in Lithuania’s family policy through qualitative legal document content analysis and semi-structured interviews with single mothers. It reveals historical policy biases favouring nuclear families, resulting in marginalised single-mother households despite recognising their economic challenges. Analysis of single mothers’ experiences shows how stigmatization negatively impacts these families’ well-being and political representation, hindering rights advocacy.